P–403 Sodium tungstate increases embryo adhesion through a direct effect on endometrial cells. (6th August 2021) - Canals, I; Cotán, D; Torres, R; Horcajadas, J A; Arbat, A
Abstract: Study question: Does sodium tungstate treatment induce a change in endometrial cells' capacity to implant trophoblasts? Summary answer: Administration of sodium tungstate to endometrial cells increases trophoblast adhesion. What is known already: Sodium tungstate (ST) has shown its capacity to modulate the activity of cytokines, such as leptin, an activator of an obligatory signalling cascade in the embryo-implantation process. STAT3, a signal transducer molecule critical for the embryo implantation process, is also known to be activated by ST. Still, ST's effect on implantation using biological systems has never been studied. Embryo implantation process and endometrium roles are complicated to study in vivo due to a lack of animal models and appropriate techniques. In vitro techniques using immortalised cell lines allows a first approach to study early implantation stages, such as embryo adhesion. Study design, size, duration: An in vitro study was carried out using a human endometrial carcinoma cell line (HEC–1-A) treated with sodium tungstate for 24 and 48h, and choriocarcinoma cell spheroids (JAr). Different times of treatment and concentrations were studied. Each experiment was performed in triplicate. Participants/materials, setting, methods: Confluent endometrial HEC–1-A cultures were treated with ST at concentrations (0–150mM) and withaferin A (1mM), negative control for embryo adhesion. After the treatment period, HEC–1-A cultures were washed with ST-free culture medium to eliminate ST. Immediately, 15 JAr trophoblast spheroids were added to cultures and coincubated with gentle agitation for 30, 60 and 90 minutes. An inverted light microscope was used to count adhered and floating spheroids, and determine the trophoblast adherence ratio. Main results and the role of chance: HEC–1-A cells treated with ST showed normal morphology and growth at all doses except 150mM. At the highest dose tested, the cells' culture was still viable (negative blue trypan staining) and maintained morphology, but the adhesion to the plate surface was affected. Doses from 0.15 to 15mM were used to perform adhesion assays. HEC–1-A cells treated with ST for 24h showed an increased capacity to adhere JAr trophoblast spheroids. Adhesion rates reached significant differences at doses of 1.5 and 15mM after 60 and 90 minutes of coincubation. After 90 minutes, untreated cells reached 32.8% adhesion rate, while 1.5 and 15mM ST-treated cells reached 54.6% and 53.4% respectively (p < 0.05 ST vs untreated). Thus, the increment of trophoblast adhesion rate induced by ST reached 66%. Lower adhesion rates were observed after 60 minutes of coincubation but were also significant with a relative increase of 49.1% at 1.5mM and 50.5% at 1.5mM when compared with untreated cells (p < 0.05) Longer treatments (48h) showed similar trends to 24h-treatments, but with a lower extent of ST effect on HEC–1-A receptivity. Maximum adhesion rates were also observed at 90 minutes of coincubation and 1.5 and 15mM doses. The Mean adhesion rate increase was >40% with both doses. Limitations, reasons for caution: The current study is the first approach to evaluate sodium tungstate effect on endometrium using an in vitro model. Future research using in vivo models should be performed to assess sodium tungstate effect on endometrium receptivity and its potential as a fertility treatment. Wider implications of the findings: We conclude that the direct effect of sodium tungstate on endometrial cells increases embryo adhesion rate. These results open a new research line to a potential treatment in human reproduction management with sodium tungstate to solve the unmet need of inducing embryo implantation. Trial registration number: Not applicable